Hak Penguasaan Negara Terhadap Sumber Daya Alam Dan Implikasinya Terhadap Bentuk Pengusahaan Pertambangan - Hayati, Tri (Jurnal Hukum & Pembangunan, 2019)
Granting mining licenses brings various negative impacts in various aspects. In addition to the environmental damage that must have been caused, it also caused a lot of leakage in the revenue of state finances that should have been received by the State. Permits should be a controlling instrument in mining operations, so that they are in accordance with the philosophical meaning as mandated by Article 33 paragraph (3) of the 1945 Constitution. The meaning contained in the Article is the principle of "State's Right to Control" over natural resources and the mandate "for the greatest prosperity. people". These two things must then be used as a basis in the formulation of various policies both regulating (regeling) and those that are set (decision / licensing). Related to licensing, it has been given since the Dutch East Indies government with the form of "Concession" as stipulated in Indische Mijnwet 1899. Therefore this article wants to find a form of exploitation (including licensing) that is in accordance with the concept of the Right to Control by the State in accordance with Article 33 paragraph (3) of the 1945 Constitution.